Women Representation in First CA of Nepal (Surkhet Journal, 2014)
This paper tries to show the actual position of Nepali women in first constituent assembly of Nepal composed through the mixed electoral system in 2008. The number of women representatives of CA has been analyzed on the basis of political parties, social groups, development and ecological regions, zones, districts and age groups. Their position in CA and legislative parliament (a law making body) at the first time of Nepalese political history has been seen satisfactory with nearly 33 percent share. Political consciousness and constitutional provision of reservation have contributed to promote their representation in state’s supreme legislative body. Further efforts will be needed to maintain the present position and to increase more than it in coming days.